A Comprehensive Review on Waste Water Treatment Technologies with Special Emphasize on Biological Treatments: Life Sciences-Microbiology - Patel, Jagruti; N. Kumar, Rita; Nirmal Kumar, J.I. (International Journal of Life Science and Pharma Research, 2023)
Rapid urbanization is essential for growth and economic viability at global level, promoting the extensive industrialization. Rapid industrialization also comes with more water demand with higher water pollution. Industrial wastewater may contain heavy metal, carcinogens, mutagens and radioactive materials which must be prevented to be incorporated into the food chain. Therefore, treatments of wastewater for removal of these toxicants are a necessary and unavoidable measure. There are various modes of treatments for removal of toxicants depending on the type of contaminants. It includes physical, chemical and biological treatment alone or in combination. Here a review is carried to identify major sources of industrial wastewaters with their major pollutants. Various studies are also considered in the review for determination of the hazardous effect of wastewater on ecosystems and biological systems. Details about treatments of wastewater based on the sources were also included. More emphasis has been given on the role of microorganisms for removal of pollutants. Not limited to this, details of methods for biological removal contaminations and treatability studies are also discussed in detail. Based on the review it is found that generation of wastewater from industries must be pretreated with suitable methods before discharging into the environment to protect life on mother earth.